IMF Dependence of Midnight Bifurcation in the Thermospheric Wind at an Auroral Latitude Based on Nine Winter Measurements in Tromsø, Norway - S. Oyama; K. Hosokawa; H. Vanhamäki; A. Aikio; T. Sakanoi; L. Cai; I. I. Virtanen; K. Shiokawa; N. Nishitani; A. Shinbori; Y. Ogawa (Geophysical Research Letters)
Abstract A thermospheric wind data set from a Fabry‐Perot interferometer (630 nm) and the ion velocity from a Dynasonde in Tromsø, Norway, was analyzed for nine winter seasons to study the dynamics of the thermosphere and F‐region ionosphere at an auroral latitude. This study focused on bifurcation in the zonal component of the neutral wind and ion velocity at midnight and its dependence on the Y component of the interplanetary magnetic field (IMF). Ionospheric plasma convection patterns are evidently imprinted on the thermospheric wind variations as aspects of the westward and eastward accelerations at dusk and late morning, respectively. The zonal wind bifurcates immediately before midnight for IMF By < 0, but for By > 0, it inverts gradually into the postmidnight sector. Neutral wind streams, originating from higher latitudes, may result in the dependence because of anti‐sunward plasma flow distorted in the polar cap.